2020
DOI: 10.1080/17482631.2020.1725997
|View full text |Cite
|
Sign up to set email alerts
|

How do people with rheumatoid arthritis experience participation in a smoking cessation trial: a qualitative study

Abstract: Purpose: The aim of this study was to gain more knowledge on how people with rheumatoid arthritis (RA) experienced participation in a randomized controlled trial (RCT) testing the effect of a smoking cessation intervention since this intervention have not been tested on an RA population before Methods: We conducted a qualitative study with semi-structured individual interviews with 12 participants from the intervention group in the RCT. Results: Through thematic analysis we identified four themes: Instilling h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…', and 19% answered 'No'. In studies conducted on individuals with rheumatic diseases, the lack of knowledge status of patients on this subject has been determined, therefore it was observed that the participants wanted more information about the relationship between RA and smoking from the rheumatologist and nurse 27 . In another study, information about the effects of smoking on RA and anti-rheumatic medications played an important role in facilitating smoking cessation 28 .…”
Section: Discussionmentioning
confidence: 99%
“…', and 19% answered 'No'. In studies conducted on individuals with rheumatic diseases, the lack of knowledge status of patients on this subject has been determined, therefore it was observed that the participants wanted more information about the relationship between RA and smoking from the rheumatologist and nurse 27 . In another study, information about the effects of smoking on RA and anti-rheumatic medications played an important role in facilitating smoking cessation 28 .…”
Section: Discussionmentioning
confidence: 99%
“…This lack of connection may be due to a lack of smoking education and counseling during clinical visits [50][51][52]. This theme is echoed in a qualitative analysis of smoking cessation in people with rheumatoid arthritis, in which participants revealed the paucity of information they had received about the connection between smoking and their disease [53]. Therapies that help patients understand this link can help motivate them to initiate smoking cessation and maintain abstinence.…”
Section: Discussionmentioning
confidence: 99%